MECHANISMS OF CREATIVE SKILLS FORMATION IN STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
It is appropriate to use educational methods in the formation of students' creative skills in education. In this way, the productivity of the educational process increases, the independent thinking process of students is formed, students' passion and interest in knowledge increases, skills and competencies of solid assimilation of knowledge and free use of it in practice are formed. In the article, opinions on the creation of new ideas in the process of education and training are presented in order for students to have the qualities of creative creativity.